Susceptibility to Intracellular Infections: Contributions of TNF to Immune Defense - Li, Xinying; Körner, Heinrich; Liu, Xiaoying (Frontiers in Microbiology, 2020)
An interesting puzzle is the fact that an infection of a TNF-deficient host with pathogens such as bacteria or parasites that reside intracellularly inevitably ends fatally. Is this due to one specific role of TNF in the immune defence or are different functions responsible for this outcome. In this review we provide an update of the functions of TNF in the defense against the intracellular pathogens Listeria monocytogenes, Mycobacterium tuberculosis and Leishmania major. Furthermore, we discuss the role of TNF in the generation of pro inflammatory macrophages in mouse models of infection and summarise briefly the potential consequences of anti-TNF treatment for infectious diseases.